AB0643 CLINICAL AND ANALYTICAL DESCRIPTION OF A DERMATOMYOSITIS SERIES OF PATIENTS. (June 2019) - Camins-Fàbregas, Jordi; Esteve-Cols, Clara; Casafont-Solé, Ivette; Mateo, Lourdes; Gifre, Laia; Riveros, Anne; Aparicio-Espinar, Maria; Nack, Annika; Martínez-Morillo, Melania; Sangüesa-Gomez, Clara; Brandy-Garcia, Anahy; Prior-Español, Águeda; et al.
Abstract : Background: Dermatomyositis (DM) is an idiopathic inflammatory myopathy. The recent years has increased its knowledge thanks to best characterization of myositis-specific antibodies that correlate with different clinical phenotypes.with different clinical phenotypes. Objectives: To describe the clinical and analytical features of a series of dermatomyositis: clinical debut, clinical manifestations as well as the treatments received and the evolution of the disease. Methods: Patients diagnosed of dermatomyositis in a tertiary hospital between the years 1978-2018 according to the criteria of Bohan and Peter (1975) and according to Dalakas' classification criteria (2015). Clinical, analytical and immunological profile data were collected, as well as treatments received and the evolution of the disease. Results: A total of 59 inflammatory myopathies diagnosed between the years 1985 and 2018 were included. 46 were dermatomyositis (78%), 9 polymyositis (15%) and 4 necrotizing myositis (7%). 69% were women and 22% were smokers. Clinic started at 54 ± 17 years. The initial manifestation was pulmonary in 26.7% followed by cutaneous manifestations (24.4%) and the muscular (22.2%), while a 17.8% started skin and muscular manifestations at the same time. 45.5% behaved like a myopathic DM while a 28% as amyopathic DM and antisynthetase syndrome respectively. 38% presented interstitial involvement being the most common non-specific interstitial pneumonitis (76%)followed by usual interstitial pneumonitis (17%). In these patients, DLCO was decreased (mean of 58.9% and 13.2) as well as the FVC (average of 58%, 2.5L). 73.3% presented cutaneous involvement being the most common manifestations the Gottron papules (37.8%) and the heliotrope rash (35.6%), and up to 27% had cuticular affectacion. 64% had muscle involvement, afecting proximal and symmetrical. Neck flexors were affected in a 38% of patients while 20% had dysphagia.Only 3 patients presented dysphonia (7%) and 2 myocarditis Analytical data Conclusion: 80% received corticotherapy at a dose of mg/kg/day and 20% required high doses of metilprednisolone due to muscular involvement or pulmonary. 18% immunoglobulins and 11% cyclophosphamide. As maintenance 80% received disease modifiying antirheumatic drug in addition to corticosteroid therapy in descending doses (azathioprine 22%, dolquine 15%, tacrolimus 13.3%, rituximab 11%) due to muscle (29.9%), cutaneous (24.4%) and pulmonary involvement (22.2%). As complications, 2 cases of the syndrome were registered hemophagocytic Virtually all patients they presented pulmonary hypertension (mean 34 ± 12 mmHg). 5 patients (11.1%) were diagnosed with neoplasia, two of them after the diagnosis of DM. The mortality was 24%. 3 patients died due to a rapidly progressive pneumonitis, another 2 due to alveolar hemorrhage and three of them due to complication of the neoplastic disease. Dermatomyositis occurs in a variable way, with predominance of pulmonary, skin and muscle manifestations. They require corticotherapy and immunosuppressive treatment for maintenance, even so, mortality is high. Disclosure of interests: None declared